Pembentukan Bakat dan Minat Peserta Didik melalui Lingkungan Keluarga: Studi Kasus dalam Perspektif Psikologi Perkembangan - Annisa Febriani; Alfi Rahmi (Lembaga Yasin AlSys, 2026)
The formation of students’ talents and interests through the family environment has received attention in various studies in developmental psychology and education; however, studies that specifically explore the mechanisms through which both are formed through family interaction from the perspective of developmental psychology remain limited. This study aims to explore the role of the family environment in shaping students’ talents and interests and to identify the factors that support this developmental process. This study employed a qualitative approach with a case study design, involving 15 informants consisting of students, parents, and teachers selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, and were then analyzed using thematic analysis. The findings show that family emotional support, parenting patterns that provide space for exploration, open communication, the provision of learning facilities, and collaboration between families and schools are the main factors supporting the development of students’ talents and interests. These findings also indicate that the quality of interaction within the family has a greater influence than material support alone in encouraging the actualization of children’s potential. The conclusion of this study affirms that the family environment plays a strategic role in shaping students’ talents and interests through emotional support, effective communication, and synergy with schools. The implications of this study provide a theoretical contribution to the development of studies in developmental psychology, as well as a practical reference for parents, teachers, and educational institutions in designing parenting patterns and collaborative programs that optimally support students’ development. Future research is recommended to examine this phenomenon through a mixed-methods approach or a longitudinal design in more diverse contexts.